2012
DOI: 10.3109/15412555.2012.719050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Right Ventricular Remodeling Using Cardiac Magnetic Resonance Imaging in Co-Existent Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnea

Abstract: Untreated chronic obstructive pulmonary disease (COPD) co-existing with obstructive sleep apnea (OSA), also known as overlap syndrome, has higher cardiovascular mortality than COPD alone but its underlying mechanism remains unclear. We hypothesize that the presence of overlap syndrome is associated with more extensive right ventricular (RV) remodeling compared to patients with COPD alone. Adult COPD patients (GOLD stage 2 or higher) with at least 10 pack-years of smoking history were included. Overnight labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
1
37
0
3
Order By: Relevance
“…These patients were included in a prior published study detailing cardiovascular structure among patients with the overlap syndrome. 17 All COPD study participants also completed the Epworth Sleepiness Scale to assess daytime sleepiness 18 and the Modified Medical Research Council (MMRC) score to assess dyspnea before the polysomnography. 18 We recruited healthy volunteer controls by open enrolment using an IRB approved research website (http://clinicaltrials.partners.org/).…”
Section: Methodsmentioning
confidence: 99%
“…These patients were included in a prior published study detailing cardiovascular structure among patients with the overlap syndrome. 17 All COPD study participants also completed the Epworth Sleepiness Scale to assess daytime sleepiness 18 and the Modified Medical Research Council (MMRC) score to assess dyspnea before the polysomnography. 18 We recruited healthy volunteer controls by open enrolment using an IRB approved research website (http://clinicaltrials.partners.org/).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging (cMRI) is the gold standard for the assessment of both the morphological and functional characteristics of the RV particularly in patients with COPD in whom echocardiographic assessment is often not possible 11-14 . Furthermore, cMRI has been used to demonstrate a relationship between progressive airflow obstruction and computed tomography (CT)-detected emphysema and impaired left ventricular (LV) filling, stroke volume (SV), and RV hypertrophy 15-20 .…”
mentioning
confidence: 99%
“…This complex relationship led Sharma et al to hypothesize that right ventricular volumes and function may be worse in overlap syndrome than the individual conditions due to increased hypoxemia and/or hypercapnia, particularly during sleep. In a pilot study of 18 patients, they reported that the overlap syndrome is associated with increased RV mass and RV remodeling compared with COPD alone, and that the extent of the adverse RV remodeling correlated with the degree of nocturnal oxygen desaturation [67].…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%